The CCHamide1 Neuropeptide Expressed in the Anterior Dorsal Neuron 1 Conveys a Circadian Signal to the Ventral Lateral Neurons in Drosophila melanogaster - Yuri Fujiwara; Christiane Hermann-Luibl; Maki Katsura; Manabu Sekiguchi; Takanori Ida; Takanori Ida; Charlotte Helfrich-Förster; Taishi Yoshii (Frontiers in Physiology, 2018)
The fruit fly Drosophila melanogaster possesses approximately 150 brain clock neurons that control circadian behavioral rhythms. Even though individual clock neurons have self-sustaining oscillators, they interact and synchronize with each other through a network. However, little is known regarding the factors responsible for these network interactions. In this study, we investigated the role of CCHamide1 (CCHa1), a neuropeptide expressed in the anterior dorsal neuron 1 (DN1a), in intercellular communication of the clock neurons. We observed that CCHa1 connects the DN1a clock neurons to the ventral lateral clock neurons (LNv) via the CCHa1 receptor, which is a homolog of the gastrin-releasing peptide receptor playing a role in circadian intercellular communications in mammals. CCHa1 knockout or knockdown flies have a generally low activity level with a special reduction of morning activity. In addition, they exhibit advanced morning activity under light-dark cycles and delayed activity under constant dark conditions, which correlates with an advance/delay of PAR domain Protein 1 (PDP1) oscillations in the small-LNv (s-LNv) neurons that control morning activity. The terminals of the s-LNv neurons show rather high levels of Pigment-dispersing factor (PDF) in the evening, when PDF is low in control flies, suggesting that the knockdown of CCHa1 leads to increased PDF release; PDF signals the other clock neurons and evidently increases the amplitude of their PDP1 cycling. A previous study showed that high-amplitude PDP1 cycling increases the siesta of the flies, and indeed, CCHa1 knockout or knockdown flies exhibit a longer siesta than control flies. The DN1a neurons are known to be receptive to PDF signaling from the s-LNv neurons; thus, our results suggest that the DN1a and s-LNv clock neurons are reciprocally coupled via the neuropeptides CCHa1 and PDF, and this interaction fine-tunes the timing of activity and sleep.